2009
DOI: 10.3892/or_00000499
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and expression analysis of MGMT in advanced pediatric brain tumors

Abstract: Abstract. Insufficient response to oral temozolomide (TMZ) in children with brain tumor may depend on the repair-action of inducible O 6 -methylguanine-DNA methyltransferase (MGMT). To investigate the clinical relevance of MGMT expression, we analyzed MGMT levels by qRT-PCR and immunohistochemistry, and the methylation of gene promoter in patients with relapsed or refractory brain tumor, enrolled in an off-label trial with oral temozolomide. The drug was administered at the dose of 200 mg/m 2 /day in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Recently, great progress has been made regarding MGMT silencing because of the methylation of its promoter. On one hand, MGMT gene silencing could lead to the accumulation of tumorrelated transition mutations; on the other hand, hypermethylation of MGMT is closely associated with the tumor's increased drug sensitivity to alkylating drugs [32][33][34][35]. Therefore, MGMT methylation is a potential predictor of the tumor's response to alkylating chemotherapy [36].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, great progress has been made regarding MGMT silencing because of the methylation of its promoter. On one hand, MGMT gene silencing could lead to the accumulation of tumorrelated transition mutations; on the other hand, hypermethylation of MGMT is closely associated with the tumor's increased drug sensitivity to alkylating drugs [32][33][34][35]. Therefore, MGMT methylation is a potential predictor of the tumor's response to alkylating chemotherapy [36].…”
Section: Discussionmentioning
confidence: 98%
“…This is a suicidal reaction, wherein the methylated MGMT is inactivated, released from the DNA, and subsequently degraded in the ubiquitination pathway, instead of being recovered by demethylation. In this case, the biological effects of the cells to overcome the O 6 -AG alkylation damage are directly dependent on the concentration of molecular MGMT [29][30][31][32][33]. Studies have shown that the abnormal methylation of MGMT gene promoter was closely correlated with MGMT protein deficiency, mRNA expression deficiency, and lack of MGMT activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDS1/EVI1 fusion transcript contains a putative methyltransferase domain (21) and has been associated with differential promoter methylation in acute myeloid leukemia (28), suggesting that the observed correlation of MDS1/EVI1 fusion transcript status and MGMT promoter methylation might represent more than an epiphenomenon. Because MGMT promoter methylation status is less frequently encountered in ependymomas as compared with malignant astrocytic tumors (22) and has no proven prognostic role (29), the clinical implications of these findings remain uncertain.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies found that the methylation of the promoter of the AGT gene at 10q26, which encodes the MGMT protein, leads to transcriptional inactivation of the gene, thereby increasing chemosensitivity in gliomas, especially glioblastomas. Although methylation of tumor‐related genes, such as MGMT has been detected in other types of brain tumors, including oligodendroglial tumors, meningiomas and ependymomas, the association between methylation status of these genes and progression‐free or overall survival has not been completely examined 7, 8, 9. Nevertheless, detection of gene methylation may prove essential in not only diagnosis but also therapeutic response and prognostic prediction.…”
Section: Introductionmentioning
confidence: 99%